Pemaknaan Khalayak Pada Campaign #EndToxicMasculinity pada Media Sosial Tiktok (Studi pada Remaja di Kota Denpasar) - Paramitha, Ni Putu Nadia; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
The emergence of TikTok around 2020 in Indonesia has been growing rapidly and popularly, thus Indonesia well known as the world’s fourth largest TikTok user country. This can be considered to run an online campaign #EndToxicMasculinity on media social TikTok which is also to used to get attention from TikTok usersThis research analysed by using Stuart Hall’s Encoding-Decoding with descriptive-qualitative method through depth interview techniques with four informants who are currently an active TikTok users. The acceptance of four informants shows that they have different thoughts and meaning regarding to #EndToxicMasculinity campaign. The difference based by differences from background, knowledge, experience and circle. Audience positions are divided into three audience reading positions such as any other positions. Result of this research showed that audience’s interpretation of #EndToxicMasculinity campaign based on four informants was dominated by Dominant position. Keywords : Reception Analysis, Encoding-Decoding, Toxic Masculinity, TikTok.